Analisis Multifaktorial Indeks Pembangunan Manusia di Kecamatan Beji dan Tapos, Kota Depok - Manurung, Daniel Prawiro Pardamean; Sundoko, Husnul Fitri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyse a number of multifactorial factors that affect the Human Development Index (HDI) in Depok City, with a focus on Beji and Tapos Sub-districts. This research uses multiple linear regression analysis methods and relies on secondary data from the Depok City Statistics Bureau (BPS). The results explain that there are factors that have a significant interrelated influence on HDI in the two sub-districts, namely education, health, and per capita expenditure. In addition to these factors, there are also other factors that have a more limited impact on HDI, such as the unemployment rate and the level of urbanisation. This research is intended to provide valuable input for policy makers in an effort to improve HDI in Depok City, especially in Beji and Tapos Sub-districts.